Ets-2 Propagates IL-6 Trans-Signaling Mediated Osteoclast-Like Changes in Human Rheumatoid Arthritis Synovial Fibroblast - Singh, Anil K.; Haque, Mahamudul; Madarampalli, Bhanupriya; Shi, Yuanyuan; Wildman, Benjamin J.; Basit, Abdul; Khuder, Sadik A.; Prasad, Bhagwat; Hassan, Quamarul; Ouseph, Madhu M.; Ahmed, Salahuddin (Frontiers in Immunology, 2021)
Rheumatoid arthritis synovial fibroblasts (RASFs) contribute to synovial inflammation and bone destruction by producing the pleiotropic cytokine interleukin-6 (IL-6). However, the molecular mechanisms through which IL-6 propels RASFs to contribute to bone loss are not fully understood. In the present study, we investigated the effects of IL-6 and IL-6 receptor (IL-6/IL-6R) induced trans-signaling in human RASFs. IL6 trans-signaling caused a significant increase in tartrate-resistant acid phosphatase (TRAP)-positive staining in RASFs and enhanced pit formation by ~3-fold in bone resorption assay in vitro. IL-6/IL-6R caused dose-dependent increase in expression and nuclear translocation of transcription factor Ets2, which correlated with the expression of osteoclast-specific signature proteins RANKL, cathepsin B (CTSB) and cathepsin K (CTSK) in RASFs. Chromatin immunoprecipitation (ChIP) analysis of CTSB and CTSK promoters showed direct Ets2 binding and transcriptional activation upon IL-6/IL-6R stimulation. Knockdown of Ets2 significantly inhibited IL-6/IL-6R-induced RANKL, CTSB and CTSK expression and TRAP staining in RASFs, and suppressed markers of invasive phenotype such as Thy1 and podoplanin (PDPN). Mass Spectrometry analysis of the secretome identified 113 proteins produced by RASFs uniquely in response to IL-6/IL-6R that bioinformatically predicted metabolic reprogramming towards an osteoclast-like phenotype. These findings identified the role of Ets2 in IL-6 trans-signaling-induced molecular reprogramming of RASFs into osteoclast-like cells, which may contribute to RASFs heterogeneity.